Influence of Rice Straw and Water Hyacinth Incorporation on the Performance of Boro Rice - Al-Mamun, M. A.; Biswas, P. K.; Karim, M. F.; Hasanuzzaman, M.; Rahman, A. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at the Agronomy field, Sher-e-Bangla Agricultural University, Dhaka from November, 2009 to May, 2010 to find out the effect of rice straw and water hyacinth incorporation into the soil on the performance of boro rice. The treatments of the experiment consisted of two rice varieties viz., BRRI dhan29 and BRRI hybrid dhan2, two biomass materials viz., rice straw and water hyacinth; and three levels of biomass concentration viz., control (no biomass), 0.5 kg biomass m-2 and 1.0 kg biomass m-2. The experiment was laid out in a double split plot design with three replications having varieties in the main plot, biomass materials in the sub plot and concentrations in the sub sub-plot. Significantly higher grain yield of rice (6.90 t ha-1) and harvest index (49.27) was obtained from BRRI hybrid dhan2 as compared to BRRI dhan29 (6.08 t ha-1 and 41.27) , however, significantly higher straw yield (8.64 t ha-1) was registered with the latter variety.